Increasing university students’ awareness about winter sports - Eski, Tolga; Ozbal, Ayse Feray; Yilmaz, Dilek (Birlesik Dunya Yenilik Arastirma ve Yayincilik Merkezi, 2020)
The aim of this study is to determine awareness levels of university students attending School of Physical Education and Sports about winter sports and to examine the effects of the training program applied within the scope of the study on their cognitive, affective, psychomotor and overall awareness. The study used single-group pre-test and post-test experimental design, which is a quantitative research approach. The participants of the study were 21 students studying Kastamonu University School of Physical Education and Sports. The data collection tools used in the study were ‘Personal Information Form’, which includes questions to obtain data about their demographic information, and ‘Winter Sports Awareness Scale’. The data collected was analysed by using SPSS 20 software. According to the results of the analysis, the changes in cognitive awareness, psychomotor awareness and overall awareness levels according to pre-test and post-test scores were found to be significant while affective awareness levels were not significant. Keywords: Awareness, physical education, Skiing, sports, winter sports
Keywords: 4. Education